Microwave-assisted acid and base pre-treatment of cellulose hydrolysis - Khalid N. Jassim (College of Pharmacy / Mustansiriyah University, 2013)
The objective of this study is to hydrolysis the cellulose to glucose. The dilute acid and base hydrolysis of cellulose with hydrochloric, sulfuric acids sodium hydroxide and potassium hydroxide were undertaken alone, The conditions for the dilute acid and base hydrolysis were found to be 5% for both acids and bases at a temperature of 170°C and time 2 hours. It was found that the glucose yield by acid hydrolysis was 7.8% and by basehydrolysis was 8% .Then the dilute acid hydrolysis of cellulose with hydrochloric & sulfuric acids and the dilute base hydrolysis of cellulose with sodium and potassium hydroxide were undertaken in microwave oven for ten minutes only. The experimental data indicate that the use of microwave technology can successfully facilitate dilute acid hydrolysis and the dilute base hydrolysis of cellulose allowing high yields of glucose in short reaction times. These conditions gave a yield of 57% and 58% glucose by acids and base hydrolysis respectively. The microwave is the promising way to increase the glucose yield from cellulose